Colour television I - The Open University BBC TV; David Saunders ([United Kingdom] : The Open University, 1976)
This program looks at the techniques and technologies used in the production of color television.
Speakers: Gaby Smol, Chris Pinches.
Keywords: Color television; Television -- Transmitters and transmission